PENGEMBANGAN KOSAKATA BAHASA INGGRIS MELALUI LITERASI BACA TULIS DI SEKOLAH DASAR - Nurhayati Nurhayati; Dede Krisna; Riskawati Riskawati; Indriani Widia; Asti Aulia; Siti Fatimah; Amalia Nur Zakiah; Repi Heryanto; Mawa Nuralifa; Siti Kodariah; Hasna Kamilia Fauziah; M Zulfi TZ; R Alpin Wirayuda; Muhamad Hafid Nugraha; Gilang Gustiawan Putra (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This community service activity was carried out in Gunungbatu Village with the aim of improving the reading and writing skills and expanding the English vocabulary of elementary school students. This program applied a descriptive qualitative approach with a learning method that integrated visual and audio elements using images, word cards, and simple songs. Data was collected through participatory observation and simple vocabulary assessments before and after the activity. The results indicated a significant improvement in vocabulary mastery, from an average of 3–5 basic words at the start of the activity to over 20 words after four weeks. Additionally, students became more confident, motivated, and able to use new vocabulary in simple sentences. Therefore, the use of visual and audio methods has proven successful in improving elementary school students' English language skills and can serve as an alternative option in literacy learning processes.